Exploring the Potential of STEAM Education in Cosmetology Vocational Schools: A Pathway to Innovative Learning - Winangun, M. Mamduh; Usodoningtyas, Sri (International Journal of Trends in Mathematics Education Research, 2025)
The implementation of the STEAM approach in cosmetology learning has now become a necessity. This must be done to answer the needs of SMK Cosmetology graduates who must be ready to become makeup artists who will be faced with client problems and adaptation to rapidly developing beauty technology. In this case, students majoring in cosmetology must be equipped with problem-solving skills, critical thinking and creativity.  Through a thorough literature analysis, the author of this paper investigates the possibilities of introducing STEAM Education to cosmetology majors. While STEAM education has not been implemented in vocational education for cosmetology majors, there are seven articles about its application in vocational education at all levels. From the results of the article review, there is potential for implementing STEAM learning in Vocational Education majoring in Cosmetology because there is Science content in its curriculum structure. In addition, the implementation of STEAM in this major can be combined with a project-based learning model. An embedded approach can be used to execute STEAM education, with science-based content on anatomy and physiology serving as the foundational literacy that is created, with additional competences serving as support.